Sistema integrado para la gestión de indicadores de calidad en la facultad de Ciencias de la Ingeniería y Aplicadas Módulo Estudiantes. - Toapanta Guanoluisa, Edwin Paúl (2018)
The present research, Public Institutions in Ecuador still process information inherent to their management activities manually, which leads to losses of time in the delivery of information, accumulation of workload and storage of documents that require large amounts of space for files. For this reason, it is considered important the automation of its administrative management procedures that allows the optimization of its activities related work environment. The purpose of this technological proposal is to develop a system that automates the management of student indicators for the Faculty of Engineering and Applied Sciences. For the development of the research, the software development methodology SCRUM was applied, which allowed to comply with the construction of the system in phases of analysis, design, implementation and testing. The technologies implemented to meet the project's objectives were .NET with the MVC 5 Framework and Sql Server Management Studio 2012, which allowed the coding of the program to be divided by functionality. As a result, a computer application is obtained that determines, by means of a massive load, permanence, dropout and degree rates for students of the Faculty of Engineering and Applied Sciences. It is concluded that this type of systems will help the academic authorities in the management of quality indicators regarding student information, for decision making.